Sining biswal a documentary on the Spanish influence on Philippine visual arts - Jose, Regalado Trota; Tiongson, Lito (Tuklas sining series., 1992)
The Spanish, with the help of the Church and the new ilustrado class, introduced and developed visual art forms that later became dominant in Philippine culture. Sculpture, painting, print, furniture, metalwork, textile arts and fiesta decor are featured in this documentary.